Roman portraiture and biometric identification - Schofield, Damian; Lorenz, Katharina; Davy-Jow, Stephanie; Anderson, Matthew (2012)
This project utilised three-dimensional scanning technology in the study of ancient Roman art and archaeology: Roman representations of faces executed in marble.